Microglia and lipids: how metabolism controls brain innate immunity. (April 2021) - Chausse, Bruno; Kakimoto, Pamela A.; Kann, Oliver
Abstract: Microglia are universal sensors of alterations in CNS physiology. These cells integrate complex molecular signals and undergo comprehensive phenotypical remodeling to adapt inflammatory responses. In the last years, single-cell analyses have revealed that microglia exhibit diverse phenotypes during development, growth and disease. Emerging evidence suggests that such phenotype transitions are mediated by reprogramming of cell metabolism. Indeed, metabolic pathways are distinctively altered in activated microglia and are central nodes controlling microglial responses. Microglial lipid metabolism has been specifically involved in the control of microglial activation and effector functions, such as migration, phagocytosis and inflammatory signaling, and minor disturbances in microglial lipid handling associates with altered brain function in disorders featuring neuroinflammation. In this review, we explore new and relevant aspects of microglial metabolism in health and disease. We give special focus on how different branches of lipid metabolism, such as lipid sensing, synthesis and oxidation, integrate and control essential aspects of microglial biology, and how disturbances in these processes associate with aging and the pathogenesis of, for instance, multiple sclerosis and Alzheimer's disease. Finally, challenges and advances in microglial lipid research are discussed.